2018
DOI: 10.7906/indecs.16.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Internet Marketing as a Business Necessity

Abstract: The pace at which marketing discipline evolves each year is challenging for both individual marketing experts and companies as systems, which are permanently competing for global consumers. With the development of the Internet as the main channel and best opportunity for the implementation of the optimal "one-to-one" marketing model, Internet marketing as a new area of marketing theory and practice has emerged and is constantly improving. On the other side, the power and attractiveness of online surrounding ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 12 publications
0
16
0
2
Order By: Relevance
“…With the growing importance of internet marketing, different opportunities and challenges have occurred the organizations. Therefore, one needs to focus on new online marketing strategies (Grubor & Jaksa, 2018). Dynamic changes that is taking place because of the digital technology has forced higher education institutions to rethink their way of marketing.…”
Section: Discussionmentioning
confidence: 99%
“…With the growing importance of internet marketing, different opportunities and challenges have occurred the organizations. Therefore, one needs to focus on new online marketing strategies (Grubor & Jaksa, 2018). Dynamic changes that is taking place because of the digital technology has forced higher education institutions to rethink their way of marketing.…”
Section: Discussionmentioning
confidence: 99%
“…Grubor and Jakša [25] propose the term 'internet marketing', as a subset of digital market-ing that particularly uses the Internet for achieving the same goals. Constantinides [26], on the other hand, suggests the Web-Marketing Mix framework, in which the website of the organization is the cornerstone of any Internet marketing strategy.…”
Section: Methodsmentioning
confidence: 99%
“…The upgraded big data algorithm is utilized to analyze and derive frequent patterns. Grubor et al reported primarily focusing on leading Indian businesses utilizing Instagram to establish a strong brand and the advantages and future potential [17]. Social media has become the most crucial connection in human lives nowadays, both for interacting with one another and marketing enterprises.…”
Section: Background To the Digital Marketing Strategiesmentioning
confidence: 99%